Potential prebiotic effect of two Atlantic whole brown seaweeds, Saccharina japonica and Undaria pinnatifida, using in vitro simulation of distal colonic fermentation - Lopez-Santamarina, Aroa; Sinisterra-Loaiza, Laura; Mondragón-Portocarrero, Alicia; Ortiz-Viedma, Jaime; Cardelle-Cobas, Alejandra; Abuín, Carlos Manuel Franco; Cepeda, Alberto (Frontiers in Nutrition, 2023)
Two brown seaweeds (Saccharina japonica and Undaria pinnatifida) were characterized in terms of their nutritional and mineral composition, as well as their potential to modify the human gut microbiota. Nutritional analysis of these seaweeds showed that they comply with the criteria set out in European legislation to be labeled "low fat," "low sugar," and "high fiber." Mineral content analysis showed that 100 g of seaweed provided more than 100% of the daily Ca requirements, as well as 33%–42% of Fe, 10%–17% of Cu, and 14%–17% of Zn requirements. An in vitro human digest simulator system was used to analyze the effect of each seaweed on the human colonic microbiota. The gut microbiota was characterized by 16S rRNA amplicon sequencing and short-chain fatty-acid analysis. Seaweed digestion and fermentation showed beneficial effects, such as a decrease in the phylum Firmicutes and an increase in the phyla Bacteroidetes and Actinobacteria. At the species level, seaweed fermentation increased the proportion of beneficial bacteria such as Parabacteroides distasonis and Bifidobacterium. In terms of metabolic pathways, no significant differences were found between the two seaweeds, but there were significant differences with respect to the baseline. An increase in short-chain fatty-acid content was observed for both seaweeds with respect to the negative control, especially for acetic acid. In view of the obtained results, S. japonica and U. pinnatifida intake are promising and could open new opportunities for research and application in the fields of nutrition and human health.